The relation between emotional quotients (EQ) towards physical education performance in junior high school in Yogyakata - Febri Sulistiya; Komarudin Komarudin (Nicolaus Copernicus University in Toruń, 2020)
Abstract This research aims to know the relation between Emotional quotients toward the performance of physical education for Junior High schooler. The researcher used correlational method with regression approach. Based on Komasis, the regress equation that obtained is Y = 0,03 X1 + 2,708 with coefficient of determination (R) 0,0745. It means that 7,45% physical education performances are affected by emotional quotient. Meanwhile, the other 92,55% affected by other factors that will not discussed in this research. Based on the research, the researcher concluded that emotional quotient has a significant role in physical education performance. Keywords: Emotional Quotient (EQ), Study Performance